Comparing the individual and combined effects of nano zinc and conventional zinc fertilization on growth, yield, phytochemical properties, antioxidant activity, and secoisolariciresinol diglucoside content in linseed - Ragini Singh; Peer Saffeullah; Shahid Umar; Sageer Abass; Sayeed Ahmad; Noushina Iqbal (Plant Nano Biology)
Zinc sulfate (ZnSO4), a conventional Zn fertilizer, is widely used due to its high solubility and ease of application. In contrast, nano Zn represents an innovative approach, utilizing nanoscale particles to enhance Zn bioavailability and uptake efficiency. This study compares these two Zn fertilizers regarding their impact on plant growth, yield, Zn uptake, and overall crop quality. In our study, we explored the potential of nano Zn and ZnSO4 by applying two different doses of each (100, 1000 ppm ZnO NP and 30, 50 kg ha−1 ZnSO4) both individually and in combination, to linseed accession. The results obtained showed the potential of nano Zn over conventional Zn fertilizer in terms of enhanced linseed growth and yield together with greater antioxidants enzyme, oil content, protein content, Zn accumulation, secoisolariciresinol diglucoside (SDG) content, and the accumulation of bioactive metabolites. Nanoscale ZnO (with particle size less than 100 nm) at a 1000 ppm concentration sped up growth, yield, increased SDG content, and antioxidant activity. However, when nano Zn (1000 ppm) was applied in combination with ZnSO4 (30 kg ha−1), it maximally enhanced plant fresh and dry weight, photosynthesis, and yield compared to their individual treatment. The combined application increased seed yield by 4.55 folds compared to the control. The treated plants were assessed for SDG content using liquid chromatography-mass spectrometry analysis (LC-MS), which showed maximum increase with 1000 ppm ZnO NP. SDG is a type of lignan known for their antioxidant properties and potential health benefits paving way for its pharmaceutical importance.